PENGARUH KOSENTRASI PELET TEPUNG JAGUNG, TEPUNG DAUN KELOR DAN DAUN LAMTORO SEBAGAI SUMBER PAKAN TAMBAHAN TERHADAP PERTUMBUHAN IKAN NILA (Oreochromisniloticus) - ANTASALAM AJO; ISMAIL FAILU; SAFRIN EDY (JURNAL EKONOMI, SOSIAL & HUMANIORA, 2020)
The study aims to determine the effect of the use of various sources of feed protein on the growth of tilapia (Oreochromis niloticus) which are cultivated in the Soil Pond. While the expected benefits are to increase the growth of tilapia (Oreochromis niloticus), as well as information material for further research. The study was conducted in November to January 2020 in Liabuku Village, Bungi District, Baubau City. The experimental design used in this study was a Completely Randomized Design (RAL) with 3 treatments and 3 replications (Gasperstz, 1991), namely: (1) Treatment A with protein content of corn flour (2) Treatment B with protein content of Moringa leaf flour (3) Treatment C with protein content of lamtoro leaf flour. Concentration of corn pellet feed, moringa leaf flour and lamtoro leaf as artificial feed did not have a significant effect on the absolute growth, specific growth and survival of tilapia (Oreochromis niloticus) which were maintained in ponds. Absolute growth, specific growth and the best survival rate for treatment B (moringa leaf flour) maintained in ground pools.